Theory of basic structure: saviour of the constitution and democracy - Vijay Kumar (Delhi Aakar Books, 2025)
The present book seeks to re-evaluate the theory of basic structure at the theoretical level in the light of spurt of writings on unamendability of the foundational principles of the Constitution in the recent times from the larger canvas of democratic constitutionalism. Therefore, this book is as much an exercise in political theory as in constitutional jurisprudence. After straddling both the domain of case law and theoretical exploration, the book argues that the features of basic structure delineated by the Supreme Court on case to case basis in the last 50 years correspond with the Idea of India. The book has privileged the identity grounded in the definition of citizenship in the Constitution by subordinating the identity rooted in scripted categories.
Keywords: Constitution of India